Plexiform fibrohistiocytic tumor-report of one case with regional lymph node metastasis - Yi-Chun Chen; Cheng-Hsiang Hsiao; Jau-Shiuh Chen; Yi-Hua Liao (Wolters Kluwer Medknow Publications, 2010)
A plexiform fibrohistiocytic tumor (PFT) is a rare mesenchymal neoplasm primarily occurring in children and young adults. PFTs have been classified as fibrohistiocytic tumors of intermediate malignancy because of the high local recurrence rate and possible lymph node and distant metastasis. Histologically, PFTs are poorly demarcated dermal-to-subcutaneous tumors composed of small nodules or cellular clusters with a characteristic plexiform arrangement. We report a 17-year-old girl presenting with a nasal root tumor and concurrent cervical lymphadenopathy. Light microscopy and immunohistochemical findings were compatible with a PFT, for both the nasal root tumor and the cervical lymph nodes. Under the diagnostic impression of a PFT with neck lymph node metastasis, the patient underwent wide excision of the primary tumor and cervical lymph node dissection, followed by concurrent chemo-radiotherapy. During a 4-year follow-up, no evidence of recurrence was noted. We also review the previously published cases of PFTs with metastasis.